The effects of measurement parameters on the cancerous cell nucleus characterisation by atomic force microscopy in vitro. (21st April 2022) - Zhu, Jiajing; Tian, Yanling; Yan, Jin; Hu, Jing; Wang, Zuobin; Liu, Xianping
Abstract: Cancer is now responsible for the major leading cause of death worldwide. It is noteworthy that lung cancer has been recognised as the highest incidence (11.6%) and mortality (18.4%) for combined sexes among a variety of cancer diseases. Therefore, it is of great value to investigate the mechanical properties of lung cancerous cells for early diagnosis. This paper focus on the influence of measurement parameters on the measured central Young's moduli of single live A549 cell in vitro based on the force spectroscopy mode of atomic force microscopy (AFM). The effects of the measurement parameters on the measured central Young's moduli were analysed by fitting the force–depth curves utilising the Sneddon model. The results revealed that the Young's moduli of A549 cells increased with the larger indentation force, higher indentation speed, less retraction time, deeper Z length and lower purity percentage of serum. The Young's moduli of cells increased first and then decreased with the increasing dwell time. Hence, this research may have potential significance to provide reference for the standardised detection of a single cancerous cell in vitro using AFM methodologies. Lay description: Cancer is now responsible for the majority leading cause of death worldwide and it is noteworthy that lung cancer has been recognised as the highest incidence (11.6%) and mortality (18.4%) for combined sexes among a variety of cancer diseases. Therefore, it is of great value to investigate the mechanical properties of lung cancerous cells for early diagnosis. This paper primarily investigated the morphological properties and the influence of measurement parameters on the measured local elastic moduli of single live A549 cell in vitro using the AFM‐based force spectroscopy mode. In practice, there are many factors for incorrect or inaccurate experimental results using AFM to measure the characteristics of live cells, such as non‐homogeneous nature of cells, probe geometry and size, mechanical analysis model, substrate stiffness and different measurement parameters. The various measurement parameters have become the huge impact factor to influence the measurement result. Hence, this research may have potential significance to provide reference for the standardised detection of a single cancerous cell in vitro using AFM methodologies.